The Effects of Specific Exercise Modalities on Tension-Type Headache Symptoms: A Narrative Review - Wachowska, Marta; Chmielowiec, Julia; Czyżewicz, Zuzanna; Dworak, Kinga; Trędota, Natalia; Posid, Dominika; Lewczuk, Michał; Dańda, Karol; Chludek, Aleksandra; Chobot, Barbara (Quality in Sport, 2026)
Background: Tension-type headache (TTH) is the most prevalent primary headache disorder, characterized by a complex pathophysiology involving pericranial muscle tenderness, craniocervical muscle weakness, and central sensitization. While pharmacological treatments are common, their long-term efficacy is limited by potential adverse effects and the risk of medication-overuse headache. Aim: This narrative review aims to evaluate the influence of specific exercise modalities—including strength training, aerobic exercise, and low-intensity interventions such as yoga, pilates, and relaxation exercises—on TTH frequency, intensity, and duration. Material and methods: A comprehensive literature search was conducted using PubMed/MEDLINE, Google Scholar, and Cochrane Library for peer-reviewed studies published between 2015 and 2025. The analysis focused on active physical interventions in adult patients with TTH. Results: Strength training targeting the deep neck flexors and extensors effectively reverses muscle atrophy and corrects the cervical extension/flexion ratio, particularly when combined with postural correction. Aerobic exercise modulates central pain processing, showing comparable efficacy to body awareness therapies. Novel interventions focusing on the posterior kinetic chain (hamstring relaxation) and progressive muscle relaxation show promise in addressing widespread hyperalgesia. Conclusions: Physical training is a potent, disease-modifying intervention for TTH. Optimal outcomes require long-term (3–6 months) multimodal protocols that combine local biomechanical correction with systemic pain modulation.